Semiotics Analysis of 'Gemoy' Animations Political Communication Strategy in Efforts to Change Prabowo-Gibran's Branding - Yarnis, Yarnis; Muksin, Nani Nurani (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This research will focus on the symbolic interaction of the 'gemoy' character carried by the Prabowo-Gibran pair. This research uses a qualitative research method that uses a literature review by using various data and information about the